Essential oils from fruits of Zanthoxylum armatum exhibit antioxidant, anti-inflammatory, and anticancer properties by inhibiting p38-MAPK pathway - Shirani Punniyamoorthy; Achyut Adhikari; Janaki Baral; Gagandeep Singh; Yuba Raj Pokharel (Results in Chemistry)
Essential oils from Zanthoxylum armatum fruits, known for their therapeutic properties, were extracted from three regions of Nepal: Myagdi (EO1), Surkhet (EO2), and Salyan (EO3). GC–MS analysis identified linalool as the predominant compound (58.31 %, 58.45 %, and 80.37 % in EO1, EO2, and EO3, respectively), along with limonene and trans-methyl cinnamate. These oils exhibited strong antioxidant activity as assessed by ferric reducing power, phosphomolybdenum capacity, and NO scavenging along with anti-inflammatory effects by reducing albumin denaturation and NO production in LPS-induced RAW 264.7 cells. Cytotoxicity assays showed dose-dependent effects against lung (NCI-H460), skin (A431), and prostate (PC3) cancer cells, with the highest activity in NCI-H460 (IC50 = 78.5 μg/mL). Mechanistic studies revealed reduced clonogenicity, inhibited migration, S-phase cell cycle arrest, and apoptosis via downregulation of RACK1, p38 MAPK, c-MYC, Vimentin, and Bcl-2. In silico docking confirmed strong interactions of linalool and limonene with p38 MAPK and c-MYC, respectively. These results highlight the potential of Z. armatum essential oils for antioxidant, anti-inflammatory, and anticancer applications.